Assessing the Impact of BIDA Training Extension Program: A Foundation for Enhancing Local Governance - Gladys Mayette S. Patricio; Apolinario G. Ballenas Jr; Irene A. Robles; Nolan M. Yumen (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
Good governance at the barangay level is critical for fostering community development, ensuring accountability, and delivering efficient public services. However, many rural barangays in the Philippines face challenges such as outdated record-keeping systems, limited access to technology, and insufficient technical capacity among officials, which hinder the effective delivery of services and undermine transparency. This study evaluates the implementation and impact of the Barangay InfoSystems for Development and Accountability (BIDA) program, a capacity-building initiative under the Community Empowerment through Science and Technology (CEST) program of the Department of Science and Technology (DOST). The program was implemented in Barangays Mag-Aba, Pandan, and Idio, Sebaste, Antique, aiming to equip officials with digital tools and practical skills to enhance administrative processes, improve transparency, and foster accountability. A convergent parallel mixed-methods research design was used to gather data from 40 participants, including barangay captains, kagawads, secretaries, treasurers, barangay health workers, and Sangguniang Kabataan chairpersons. Quantitative data were analyzed using descriptive and inferential statistics, while thematic analysis was applied to qualitative responses. Results revealed that 90% of respondents reported improved record-keeping, 85% noted enhanced financial reporting, and 80% highlighted streamlined administrative processes. However, challenges such as limited device access (70%), connectivity issues (60%), and insufficient training duration (50%) were identified. The study concludes that the BIDA program significantly improved governance efficiency and accountability in the target barangays. Key recommendations include adding devices, providing additional training, and improving internet access. These insights can help replicate the program in other rural Philippine communities, supporting local governance modernization.